In situ revascularisation for femoropopliteal graft infection: ten years of experience with silver grafts. (October 2014) - Matic, P; Tanaskovic, S; Babic, S; Gajin, P; Jocic, D; Nenezic, D; Ilijevski, N; Vucurevic, G; Radak, Dj
Purpose: The purpose of this study was to analyze clinical outcome of patients for femoropopliteal graft infection who were treated by in situ reconstruction with a silver-coated prosthesis. Basic methods: From December 2001 to December 2011, 27 patients were treated for femoropopliteal graft infection. Twenty patients (74%) were male and seven (26%) were female. Mean age was 65 years. The primary endpoint was recurrence of infection. Secondary endpoints were early and late mortality and morbidity, primary graft patency, major amputation rates and patient survival. Principal findings: Early reinfection occurred in 11% and late in 8% of patients. Perioperative mortality was 7% and late was 4%. Above-knee amputation was performed in 4% of patients during early postoperative course and in 12% of patients during follow-up. Early and late graft patency was 96% and 72%, respectively. Conclusions: Results of in situ implantation of silver-coated grafts for femoropopliteal prosthesis infection are according to our opinion acceptable, but the risk of reinfection remains.